Structural Bias and the Need for Substantive Review - Julian Velasco (Washington University Law Quarterly, 2004)
One of the fundamental debates in corporate law pits the authority of the board of directors to make business decisions without judicial interference against the accountability of directors to shareholders for their decisions. The business judgment rule attests to the value ascribed to authority by providing only limited judicial review for claims of breach of the duty of care, while the entire fairness test demonstrates the value ascribed to accountability by providing far more exacting scrutiny for claims of breach of the duty of loyalty. In cases involving structural bias, however, neither doctrine is appropriate. Whenever the interests of directors are in conflict with those of shareholders, there is a justifiable concern that directors will pursue their own interests instead of those of shareholders. The interposition of “disinterested” directors is helpful but inadequate because no directors are truly disinterested; at the very least, all directors are inherently interested in issues of accountability. In certain situations involving structural bias, the courts have developed intermediate standards of review for breach of fiduciary duty, but these standards are inadequate. This Article proposes and defends a standard that draws upon the insights of both the business judgment rule and the entire fairness test. The proposed standard calls for a moderate review of the merits of directors’ decisions in cases involving structural bias. A review of the substantive merit of directors’ decisions is necessary to guard against possible abuse by conflicted directors (whether conscious or unconscious), but such review must be limited in order to afford directors sufficient latitude for the exercise of business judgment. Only such an approach can provide the appropriate balance between directorial authority and accountability.
Keywords: Standard of review (Law); Social responsibility of business; Outside directors of corporations; Business judgment rule; Boards of directors; Duty of care (Law); Fiduciary duties; Hostile takeovers; Judicial review; Stockholders